Seals and baitarnames - Ali Yiğit; Aşkın Yaşar (Eurasian Journal of Veterinary Sciences)
Aim: By examining the seals that exist especially in handwritten baitarnames, what is aimed at by this study is to contribute to the road map of the manuscripts after they were written or copied. Materials and Methods: The resources of the study consisted of the seals in 32 of 46 baitarnames that exist in various libraries, related published material in Turkish and in foreign languages and Internet resources. The pieces of writing on the seals were translated into Turkish. In terms of the history of veterinary medicine, the data that are on the seals have been evaluated within the boundaries of the manuscript in which they exist. The seals were categorized into Arabic, Persian and Turkish in addition to their grouping based on ownership by foundation, person and library. Results: It was found out that there were seals in most (32) of the baitarnames examined (46). It was also found out that 20 of the seals belonged to foundations; 11 belonged to libraries and 9 of them were personal seals; in the linguistic examination, it was identified that 23 seals were in Arabic and 17 were in Turkish. Conclusion: In conclusion, it can be said that libraries and foundations have functioned as a shelter in carrying manuscripts to today and the examination of seals in manuscripts will contribute to the formation of catalogue data along with the information regarding the locations where these works are frequently visited and protected.